IMPACT OF ATMOSPHERE ON SATISFACTION AND THE BEHAVIOR INTENTION IN RESTO LA RUCOLA MEDITERRANEAN - Lorenzia Merlin Setiawan; Erna Andajani; Siti Rahayu (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2017)
This study aims to identify and analyze the influence factors of dining atmosphere of a restaurant towards satisfaction and behavioral intention. This study uses object restaurant which has a Mediterranean theme in the city of Surabaya. The data used in this study are primary data obtained by questionnaire distributed to 150 respondents who have bought and dine in the Mediterranean restaurant. The analysis used in this study is a simple linear regression analysis and multiple linear analysis. The sampling technique of this research is convenience sampling. The results showed that there is an effect of a restaurant’s dining atmosphere towards satisfaction and behavioral intention. Variables of dining satisfaction affect the intention of behavior as well. In this study multiple linear regression tests were carried out for the four atmosphere dimensions of restaurants. It was found that the dimensions of facility aesthetics of restaurant’s atmosphere did not significantly influence dining satisfaction and behavioral intention.